Klotho regulates CA1 hippocampal synaptic plasticity. (7th April 2017) - Li, Qin; Vo, Hai T.; Wang, Jing; Fox-Quick, Stephanie; Dobrunz, Lynn E.; King, Gwendalyn D.
Highlights: Klotho is detected in synaptosomes isolated from hippocampus. Enhanced CA1 paired-pulse facilitation and long-term potentiation precede cognitive impairment in Klotho-deficient mice. Klotho overexpression does not affect pre-synaptic plasticity but decreases long-term potentiation at CA1 synapses. Abstract: Global klotho overexpression extends lifespan while global klotho-deficiency shortens it. As well, klotho protein manipulations inversely regulate cognitive function. Mice without klotho develop rapid onset cognitive impairment before they are 2 months old. Meanwhile, adult mice overexpressing klotho show enhanced cognitive function, particularly in hippocampal-dependent tasks. The cognitive enhancing effects of klotho extend to humans with a klotho polymorphism that increases circulating klotho and executive function. To affect cognitive function, klotho could act in or on the synapse to modulate synaptic transmission or plasticity. However, it is not yet known if klotho is located at synapses, and little is known about its effects on synaptic function. To test this, we fractionated hippocampi and detected klotho expression in both pre and post-synaptic compartments. We find that loss of klotho enhances both pre and post-synaptic measures of CA1 hippocampal synaptic plasticity at 5 weeks of age. However, a rapid loss of synaptic enhancement occurs such that by 7 weeks, when mice are cognitively impaired, there is no difference from wild-type controls. Klotho overexpressing mice show no early life effects on synaptic plasticity, but decreased CA1 hippocampal long-term potentiation was measured at 6 months of age. Together these data suggest that klotho affects cognition, at least in part, by regulating hippocampal synaptic plasticity.